Dissection in the subgaleal and subperiosteal plane: Implications on scalp wound healing. Issue 3 (June 2013) - Rapp, Scott J.; Jones, Donna C.; Billmire, David A.; Taylor, Jesse A.
Abstract Craniofacial reconstruction often involves the use of dissection in the subperiosteal or subgaleal plane to access the cranial vault and facial skeleton. Clinically, physical changes to the periosteal layer and underlying cortex were observed in the re-operative field. This article compares aspects of wound healing, structural integrity of the progenitor periosteal layer, and underlying bony changes when elevating a subgaleal or subperiosteal flap in a Lewis rat calvarial model. Cranial dissection in the subperiosteal or subgaleal plane was performed on 14 Lewis rats. En bloc resection of the calvarium and overlying soft tissue was harvested at days 0, 1, 3, 7, 14, 28, and 56. Samples underwent SEM imaging and were analysed histologically after trichrome and haematoxylin and eosin staining. One sample of native periosteum underwent cellular expansion to determine periosteal cell regenerative capability. Up to 56 days, subperiosteal dissection results in diffuse hypercellularity within the cambial layer (p < 0.001). There are irregular cortical changes at the periosteal interface and increased disorganised bone remodelling at the temporal ridges. Subgaleal dissection did not reveal any underlying bony changes, and cell counts were not significantly different from controls (p < 0.001). Subperiosteal dissection causes structural and cellular changes to the periosteum and underlying bone composition with a possible influence on its regenerative capability.